1992
DOI: 10.3928/0098-9134-19921201-06
|View full text |Cite
|
Sign up to set email alerts
|

POSTMENOPAUSAL WOMEN: Factors in Osteoporosis Preventive Behaviors

Abstract: Osteoporosis is a serious health hazard mainly affecting postmenopausal and elderly women. Osteoporotic fractures are one of the leading causes of morbidity and death in the elderly population. Prevention of further loss of bone mass in postmenopausal women can be achieved if women take estrogen replacement therapy, consume adequate levels of calcium, exercise regularly, and practice healthy lifestyle behaviors. Elderly women need to follow the same strategies as postmenopausal women with more emphasis on prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 23 publications
4
19
0
Order By: Relevance
“…Research has primarily focused on prevention among menopausal and postmenopausal women (e.g., Ali & Bennett, 1992;Cook, Noteloviz, Rector, & Krischer, 1991) . Greater knowledge of OP has been found to be positively associated with age (Taggart & Connor, 1995).…”
Section: "I Never Realised How Little I Knew!": a Pilot Study Of Ostementioning
confidence: 99%
“…Research has primarily focused on prevention among menopausal and postmenopausal women (e.g., Ali & Bennett, 1992;Cook, Noteloviz, Rector, & Krischer, 1991) . Greater knowledge of OP has been found to be positively associated with age (Taggart & Connor, 1995).…”
Section: "I Never Realised How Little I Knew!": a Pilot Study Of Ostementioning
confidence: 99%
“…Riffle et al (1989) reported an average score of 135 for older Appalachians, postmenopausal women had a mean score of 131 (Ali & Bennett, 1992), rural women's average ranged from 126 to 133 (Gillis & Perry, 1991), and midlife women scored 138 (Duffy, 1988).…”
Section: Discussionmentioning
confidence: 98%
“…The HPLP I1 has been used to ascertain the health-promoting lifestyles of various populations including older adults (Foster, 1992;Riffle, Yoho, & Sams, 1989;Walker, Volkan, Sechrist, & Pender, 1988), employed men and women (Duffy, 1989;Lusk, Kerr, &Ronis, 1995;Pender et al, 1990), midlife women (Duffy, 1988), postmenopausal women (Ali & Bennett, 1992), African American women (Ahijevych & Bernhard, 1994), and rural women (Gillis & Peny, 1991). The instrument has not been used specifically to study the health-promoting activities of women in crisis situations, such as homelessness, yet the extensive sampling of women in previous studies lends credence to the use of this tool.…”
Section: Instruments and Data Collectionmentioning
confidence: 99%
“…3) On the positive side, shared life experiences are reported to foster a sense of camaraderie and to provide valuable social support for osteoporosis patients in small (three to four persons), same-sex groups (Gold et al, 1991). However, it is believed that the lack of public knowledge about behaviours which may prevent osteoporosis is the root cause for the perpetuation of these risk factors (Ali & Bennett, 1992;Cook, Notelovitz, Rector, & Krischer, 1991). The cultural element of the environment According to the CMOP, cultural elements of the environment include the ethnic, racial, ceremonial and routine practices, based on ethos and value systems of particular groups (Law et al, 1997, p. 46).…”
Section: The Social Element Of the Environmentmentioning
confidence: 99%